Community Empowerment Regarding Catfish Cultivation Using the Biofloc Method in Temba Lae Village, Dompu Regency - Rubianti, Irma; Wiraningtyas, Agrippina; olahairullah, olahairullah; Wahyu Wijaya, I Made; Widnyana, i Ketut; Pasmidi Ariati, Putu Eka (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2024)
This activity aims to empower the economy of the residents of Temba Lae Village, Dompu Regency by developing catfish cultivation. The method used in this activity is a participatory approach. This activity involved the So Tolo Pari Farmers Group, totaling 25 people, as partners and research subjects. This study includes steps: socialization, training, mentoring, evaluation, and strengthening. Data was collected through secondary data, direct observation, interviews with key informants, and documents. Data were analyzed using data reduction techniques, data presentation, and drawing conclusions. The research results show that community economic empowerment through the development of catfish cultivation has succeeded in increasing the community's knowledge, skills, economic and social aspects. Factors that influence the success of community empowerment are community support and active participation, stakeholder support and cooperation, availability and suitability of resources, and the application of participatory methods. The long-term impact of community empowerment is as follows: the community can develop an independent, sustainable and competitive catfish farming business, the community is able to improve the quality of life, independence and welfare; The community can contribute to regional development, especially in the fisheries sector.